Mesothelioma of the atrioventricular node. - Nishida, K (1985)
A patient with Mobitz type 2 heart block caused by a mesothelioma of the atrioventricular node died of a subarachnoid haemorrhage at the age of 33 two years after implantation of a permanent pacemaker. Mesothelioma of the atrioventricular node is rare, and reported cases have all been diagnosed post mortem. Mesothelioma of the atrioventricular node should be considered in the differential diagnosis of heart block in children or young adults. This is the first case to be reported in Japan.